A dinâmica identitária no tratamento das relações amorosas pelo Projeto Tribalista - Rêgo, Carmem Sílvia de Carvalho (2023)
This work describes the tribalist subject identity dynamics as a counterprogram of the Brazilian song romantic tradition, based on the semiotic analysis of songs that address the theme of romantic relationships. For this objective, we considered as a corpus the songs disseminated in the two albums of the Tribalistas project (2002 and 2017), composed by Arnaldo Antunes, Marisa Monte and Carlinhos Brown, which cover the theme in focus. In total, we selected six songs for analysis – four from the 2002 album and two from the 2017 album –, which we examined in search of: i) Deduct the privileged verbal and melodic enunciative operations and their effects on the projected identity(ies); ii) Check whether it is possible to affirm a homogeneous identity in the songs in the Tribalistas project that focus on romantic relationships; and iii) Compare the image-end of the subject(s) constituted in the Tribalistas project to that of the subject traditionally constituted in Brazilian romantic songs. This work is based on the theoretical-methodological contributions of Zilberberg (2006 [1988]; 2011 [2006]), Tatit (1994, 1997) and Saraiva (2012; 2011), whose proposals are intertwined in a very favorable way to the development of this work, since they advance harmoniously in the appropriation of discursive semiotics, a theory founded by Greimas (1976 [1966]), sometimes aspectualizing it, as Zilberberg does in the tensive perspective; sometimes specializing it – already from a zilberbergian perspective –, as Tatit does with the semiotics of the song; sometimes integrating these approaches of the base into the expanded view of a central category to the model, following the example of the identity dynamics proposed by Saraiva. We recognize a homogeneous identity projection, particularly related to the tribalist discourse, but which maintains affinities with the romantic tradition. In effect, the image-end constructed by the Tribalistas project is that of a non-idealized, independent and egalitarian subject, who constitutes an alternative, although not excluding, to the romantic tradition subject: idealized, emotionally dependent and incomplete. Based on the tradition enunciative program, the tribalist subject concessively installs his own program and thus constitutes himself in the romantic song discourse. Through strategies such as overlapping narrative sequences, pluri-isotopies or overdetermination, the Tribalistas project songs enunciate from the tradition values, to bring out values that were not foreseen in the dominant sequence.